Osteocyte intrinsic TGFβ signaling regulates bone quality through perilacunar/canalicular remodeling - Dole, Neha S. (Cell Rep, 2017)
Poor bone quality contributes to bone fragility in diabetes, aging, and osteogenesis imperfecta. However, the mechanisms controlling bone quality are not well understood, contributing to the current lack of strategies to diagnose or treat bone quality deficits. TGFβ signaling is a crucial mechanism known to regulate the material quality of bone, but its cellular target in this regulation is unknown. Studies showing that osteocytes directly remodel their perilacunar/canalicular matrix led us to hypothesize that TGFβ controls bone quality through perilacunar/canalicular remodeling (PLR). Using inhibitors and mice with an osteocyte-intrinsic defect in TGFβ signaling (TβRII(ocy−/−)), we show that TGFβ regulates PLR in a cell-intrinsic manner to control bone quality. Altogether, this study emphasizes that osteocytes are key in executing the biological control of bone quality through PLR, thereby highlighting the fundamental role of osteocyte mediated perilacunar/canalicular remodeling in bone homeostasis and fragility.